2019
DOI: 10.1128/aac.02618-18
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity Evaluation of Tebipenem (SPR859), an Orally Available Carbapenem, against a Global Set of Enterobacteriaceae Isolates, Including a Challenge Set of Organisms

Abstract: The antimicrobial activity of tebipenem and other carbapenem agents were tested in vitro against a set of recent clinical isolates responsible for urinary tract infection (UTI), as well as against a challenge set. Isolates were tested by reference broth microdilution and included Escherichia coli (101 isolates), Klebsiella pneumoniae (208 isolates), and Proteus mirabilis (103 isolates) species. Within each species tested, tebipenem showed equivalent MIC 50/90 values to those of meropenem (E. coli MIC 50/90 , Յ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…formulations, highlighting the unmet need for an oral formulation of carbapenems to treat serious infections due to MDR pathogens. Results from in vitro studies demonstrated that tebipenem has potent antibacterial activity against MDR strains, including ESBL-producing Enterobacteriaceae (68). Combined with the promising PK and tolerability of its orally available TBPM-PI-HBr formulation, tebipenem is well positioned to address this unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…formulations, highlighting the unmet need for an oral formulation of carbapenems to treat serious infections due to MDR pathogens. Results from in vitro studies demonstrated that tebipenem has potent antibacterial activity against MDR strains, including ESBL-producing Enterobacteriaceae (68). Combined with the promising PK and tolerability of its orally available TBPM-PI-HBr formulation, tebipenem is well positioned to address this unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) with potent in vitro and in vivo activity against A. baumannii , P. aeruginosa , and multiple clinically important species of Enterobacterales , including drug-resistant ESBL-producing and Ambler class A, B, C, and D beta-lactamase-producing strains. In vitro studies have shown SPR206 exhibits lower MICs (MIC 90 range, 0.12 to 0.5 μg/ml) than colistin and meropenem against A. baumannii , Klebsiella pneumoniae , and P. aeruginosa ( 22 27 ), and in vivo studies in thigh, lung, and urinary tract infection models in mice indicate that SPR206 achieves efficacy endpoints (reduction in bacterial burden in CFU/g) at similar or lower required doses (mg/kg) than polymyxin B (PMB) with a change from baseline in Log 10 of −4.6 for SPR206 and −2.8 for polymyxin B at 20 mg/kg ( 28 – 30 ). Nonclinical toxicology studies in mice, rats, and nonhuman primates have demonstrated that SPR206 exhibits a lower risk for kidney toxicity (nephrotoxicity) than colistin and polymyxin B, including a mouse model where no histopathological changes in the kidney were noted with SPR206 compared with all animals with polymyxin B ( 22 , 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…(90) 1 0.06–4 ESBL-positive Proteus spp. (93) 1 ≤ 0.015–32 Ceftibuten/VNRX-7145 (oral) Ceftibuten (65%) VNRX5236 (NA) Ceftibuten (75–90%) VNRX5236 (NA) Ceftibuten (57–59%) VNRX5236 (NA) Enterobacterales (205) 1 ≤ 0.015 to > 32 [ 40 ] ESBL-producing Enterobacterales (50) 0.12 ≤ 0.015 to > 32 KPC-producing Enterobacterales (50) 0.5 ≤ 0.015–8 OXA-48-like-producing Enterobacterales (50) 1 ≤ 0.015 to > 32 Enterobacterales (1066) 2 ≤ 0.25 to > 32 [ 41 ] ESBL-positive Enterobacterales (634) 0.5 ≤ 0.25 to > 32 KPC-positive Enterobacterales (61) 2 ≤ 0.25–32 Ceftibuten/ARX-1796 (oral) ARX-1796 (NA) ARX-1796 (NA) ARX-1796 (NA) ESBL-producing Enterobacterales (50) 0.06 ≤ 0.03–0.12 [ 42 ] Ceftibuten/QPX7728 (oral and IV) Ceftibuten (65%) QPX7728 (NA) Ceftibuten (75–90%) QPX7728 (NA) Ceftibuten (57–59%) QPX7728 (NA) E. coli (92) ≤ 0.015 NA [ 43 ] NA Not available …”
Section: Carbapenemsmentioning
confidence: 99%